Insights into cisplatin-induced neurotoxicity and mitochondrial dysfunction in Caenorhabditis elegans - Carmen Martínez-Fernández; Milana Bergamino; Alfonso Schiavi; David Brena; Natascia Ventura; Sebastian Honnen; Alberto Villanueva; Ernest Nadal; Julián Cerón (The Company of Biologists, 2022)
Cisplatin is the most common drug in first-line chemotherapy against solid tumors. We and others have previously used the nematode Caenorhabditis elegans to identify genetic factors influencing the sensitivity and resistance to cisplatin. In this study, we used C. elegans to explore cisplatin effects on mitochondrial functions and investigate cisplatin-induced neurotoxicity through a high-resolution system for evaluating locomotion. First, we report that a high-glucose diet sensitizes C. elegans to cisplatin at the physiological level and that mitochondrial CED-13 protects the cell from cisplatin-induced oxidative stress. Additionally, by assessing mitochondrial function with a Seahorse XFe96 Analyzer, we observed a detrimental effect of cisplatin and glucose on mitochondrial respiration. Second, because catechol-O-methyltransferases (involved in dopamine degradation) are upregulated upon cisplatin exposure, we studied the protective role of dopamine against cisplatin-induced neurotoxicity. Using a Tierpsy Tracker system for measuring neurotoxicity, we showed that abnormal displacements and body postures in cat-2 mutants, which have dopamine synthesis disrupted, can be rescued by adding dopamine. Then, we demonstrated that dopamine treatment protects against the dose-dependent neurotoxicity caused by cisplatin.